Käte Friedemann, “The Narrator in the Epic” (ENTHYMEMA, 2025)
The theoretical concept of ‘narrator’ as a mediating entity independent from the author emerged in literary studies in the early 1900s and was  fully articulated for the first time in Käte Friedemann's 1910 essay “Die Rolle des Erzählers in der Epik" ("The Role of the Narrator in Epic Literature”). Friedemann’s work, which parallels or even predates Henry James’ and Percy Lubbock's analysis of point of view, influenced Mikhail Bakhtin in the 1920s and later Franz K. Stanzel. Despite its pioneering role, it remained untranslated, which significantly limited its impact. The following pages provide the first Italian translation of the essay’s main theses, as condensed by Friedemann herself in her 1913 article “Der Erzähler in der epischen Dichtung” (“The Narrator in Epic Form”). The translation is preceded by an introduction tracking the intellectual path of the author, who grew up in an assimilated Jewish family in Berlin, was connected to Neo-Kantian circles, studied under Oskar F. Walzel in Bern and moved to Palestine in the early 1940s. Friedemann’s work, situated between the theory of the novel and narratology, represents an important voice in early 20th century literary theory, one that should be considered in its conversation with authors such as Wilhelm Dilthey or György Lukács. Furthermore, the article contributes to bringing to the fore theoretical nodes that are still under investigation today, first and foremost the problem of the narrator as a judging medium, and as such inevitably human.
Keywords: Narrator; Käte Friedemann; Theory of the Novel; Narratology; Epic; Fiction; Medium